Perlindungan Konsumen Dalam Perkembangan Financial Technology Di Indonesia - Chusnul Maulidina Hidayat; Irwan Susanto; Maliana Puspa Arum; Selin Lestari Br Karo; Ahmad Fahreza (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The rapid technological developments also have an impact on the financial industry in Indonesia. Financial service providers issue a variety of products to support their business activities and also to serve consumers who use their product services. One of the products they offer to consumers is Fintech. The Fintech innovations offered include Peer to Peer Lending (P2PL), crowdfunding, Payment Gateways, and risk and investment management. From these technological developments, new challenges arise for financial service supervisors and the government to monitor these practices in order to create an environment that is not detrimental between financial service providers and consumers. This study aims to explore the role of existing legal regulations in Indonesia in dealing with technological developments in the financial sector. The research was conducted by means of descriptive analysis and collecting review literature studies to compare and analyze consumer protection in the development of Fintech. The results of this study indicate the need for supervision by financial supervisory institutions in practice to oversee the activities carried out by financial service providers in offering their products to consumers, so that there are no violations that can harm consumers.